Productive and technological characteristics of the fiber of Suri alpacas from the Chuquibambilla Experimental Center, Puno - Arizaca Luna, Percy Fernando (2023)
This study seeks to determine the productive and technological characteristics of Suri alpaca fiber at the Chuquibambilla Experimental Center. Samples were taken from 110 alpacas during the 2022 shearing campaign, analyzed in the laboratory of INIA’s Quimsachata Experimental Station. The results showed a dirty fleece weight of 2118.64 ± 387.82 g, similar until four years and with a significant decrease from five years (P ≤ 0.05). The average wick length was 88.00 ± 16.13 mm, also similar up to four years. The mean fiber diameter (DMF) was 20.61 ± 0.33 μm, increasing with age (P ≤ 0.05), and the standard deviation of the DMF (DSDMF) was 4.74 ± 0.08 μm, with an age-related increase (P ≤ 0.05). The coefficient of variation of the DMF was 23.06%, with no significant differences between ages (P > 0.05). The comfort factor (HR) was 94.27%, decreasing with age (P ≤ 0.05). Fineness at yarn (FH) averaged 20.46 ± 0.37 μm, increasing with age (P ≤ 0.05), and the curvature index was 15.24 ± 0.37 °/mm, with a significant decrease (P ≤ 0.05). It is concluded that age influences the technological characteristics of the fiber, with positive and negative correlations of high magnitude between the variables analyzed.